Breastfeeding Practice in Tunisia: Combined Results of Multiple Indicator Cluster Surveys (2000-2018) - Mariem Nouira; Nesrine Souayeh; Mohamed Maatouk; Hajer Nouira; Anis Hasnaoui; Sondess Arfa (SAGE Publishing, 2024)
Introduction . Breastfeeding practices fall short of optimal levels globally, despite its known health benefits and World Health Organization endorsements. We aimed through this study to firstly estimate the global prevalence of principal indicators of breastfeeding practice in Tunisia. Secondly, we aimed to identify their associated factors and to assess the temporal trend of breastfeeding practice in Tunsia from 2000 to 2018. Methods . We extracted data from all available reports of Multiple Indicator Cluster Surveys (MICS) surveys conducted in Tunisia (MICS2000, 2006, 2012 and 2018) that were publicly available on the MICS UNICEF website prior to 2024. Results . Never breastfeeding prevalence was 4% (95% CI [3%-7%]) with a significant increase ( P  < 10 −3 ) from 2000 (2.4%) to 2018(7.8%). The prevalence of early breastfeeding initiation was 56% (95% CI [20%-87%]) with a significant decrease( P  < 10 −3 ) from 2006(87.4%) to 2018(31.5%). The prevalence of exclusive breastfeeding was 15% (95% CI [5%-35%]) with a significant decrease( P  < 10 −3 ) from 2000(46.4%) to 2018(13.4%). The prevalence of predominant breastfeeding was 41% (95% CI [31%-51%]) with a significant decrease( P  < 10 −3 ) from 2000(50.5%) to 2018(30.4%). The prevalence of continued breastfeeding up to the age of 2 years was 19% (95% CI [16%-22%]) with no significant decrease from 2000 to 2018( P  = .09). The mother educational level was significantly associated with early breastfeeding initiation, exclusive and predominant breastfeeding. A higher prevalence of exclusive breastfeeding was found among mothers from rural areas. Conclusions . Tunisia has been experiencing low rates of breastfeeding practice, with a concerning decline observed over the years. Addressing this issue effectively necessitates a comprehensive, multi-faceted approach that encompasses various aspects of society, healthcare, and policymaking.